Phage N15 protelomerase resolves its tos recognition site into hairpin telomeres within mammalian cells - Liew, Pei Sheng; Chen, Qingwen; Ng, Allan Wee Ren; Chew, Yee Choy; Ravin, Nikolai V.; Sim, Edmund Ui Hang; Lee, Choon-Weng; Narayanan, Kumaran (Elsevier Ltd., 2019)
Phage N15 protelomerase (TelN) cleaves double-stranded circular DNA containing a telomerase-occupancy-site (tos) and rejoins the resulting linear-ends to form closed-hairpin-telomeres in Escherichia coli (E. coli). ContinuedTelN expression is essential to support resolution of the linear structure. In mammalian cells, no enzyme withTelN-like activities has been found. In this work, we show that phage TelN, expressed transiently and stably in human and mouse cells, recapitulates its native activities in these exogenous environments. We found TelN to accurately resolve tos-DNA in vitro and in vivo within human and mouse cells into linear DNA-containing terminal telomeres that are resistant to RecBCD degradation, a hallmark of protelomerase processing. In stable cells, TelN activity was detectable for at least 60 days, which suggests the possibility of limited silencing of its expression.Correspondingly, linear plasmid containing a 100 kb human β-globin gene expressed for at least 120 h in non-β-globin-expressing mouse cells with TelN presence. Our results demonstrate TelN is able to cut and heal DNA ashairpin-telomeres within mammalian cells, providing a tool for creating novel structures by DNA resolution in these hosts. The TelN protelomerase may be useful for exploring novel technologies for genome interrogationand chromosome engineering.